2020
DOI: 10.1002/jper.20-0238
|View full text |Cite
|
Sign up to set email alerts
|

The fate of the distal papilla around tooth‐bound implant‐supported restorations in maxillary central incisor sites

Abstract: The distal papilla around tooth-bound implant-supported restorations in maxillary central incisor sites tends to exhibit an atrophied aspect after tissue maturation following the delivery of the final prosthesis. This article provides an explanation to this phenomenon, as well as a set of therapeutic considerations to minimize its occurrence and optimize the outcomes of tooth replacement therapy with dental implants in this specific anatomic location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Esposito et al's study in 1993 found a strong correlation between bone loss on adjacent teeth and tooth to implant distance in single tooth Branemark external hex implants 36 . One of the most common problems after ITRT is that the interdental papilla loses height and volume especially at the distal aspect due largely in part to physiologic process of alveolar ridge remodeling following tooth extraction 10,37–39 . The additional space offered by this narrow coronal body design increases the distance between the implant body and adjacent tooth attachment apparatus, thus enabling maintenance of the interproximal bony peak and the contours of the overlying papilla 40…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Esposito et al's study in 1993 found a strong correlation between bone loss on adjacent teeth and tooth to implant distance in single tooth Branemark external hex implants 36 . One of the most common problems after ITRT is that the interdental papilla loses height and volume especially at the distal aspect due largely in part to physiologic process of alveolar ridge remodeling following tooth extraction 10,37–39 . The additional space offered by this narrow coronal body design increases the distance between the implant body and adjacent tooth attachment apparatus, thus enabling maintenance of the interproximal bony peak and the contours of the overlying papilla 40…”
Section: Discussionmentioning
confidence: 99%
“…36 One of the most common problems after ITRT is that the interdental papilla loses height and volume especially at the distal aspect due largely in part to physiologic process of alveolar ridge remodeling following tooth extraction. 10,[37][38][39] The additional space offered by this narrow coronal body design increases the distance between the implant body and adjacent tooth attachment apparatus, thus enabling maintenance of the interproximal bony peak and the contours of the overlying papilla. 40 In addition, the acquired space between the implant platform and labial bony wall, referred to as the "gap", warrants the adequate space for bone grafting, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations